Desain Taman Atap pada Gedung SMP Pesat Bogor Berdasarkan Preferensi Pengguna - Ramadhan, Muhammad Arif; Fatimah, Indung Sitti (http://arl-faperta.ipb.ac.id/, 2024)
The increasing rate of urbanization on limited urban land has resulted in reduced Green Open Space (RTH) in urban areas. Therefore, the design of a roof garden on a school building can be a solution to increase the area of ​​green open space and a place for outdoor learning activities. This study aims to analyze the potential and constraints on the site so that a roof garden design can be developed according to user preferences. The stages of work refer to Booth (1983) which consist of project acceptance, research/analysis, concepts, and construction drawings. The design concept applied is inspired by the organically formed Falco peregrinus. The results of this study are in the form of a roof garden site plan as well as detailed pictures of the facilities used in the roof garden of building 3 SMP-SMA-SMK Informatika Pesat. The results of the study are expected to create a roof garden on a school building that can function as green open space and a refreshing area as well as a teaching and learning area.